Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Pada Periode 2013- 2014 - Hasibuan, David HM; Sushanty, Lisa (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
The implementation of good corporate governance is considered to be able of improving the banking image that previously falling off, protect the interests of the stakeholders, and improving the compliance to applicable legislations and general ethics in banking business in order to depict a healthy banking. This research is aimed to acknowledge the influence of the Board of Directors, Independent Commissioners, and Audit Committee on Net Profit Margin. This study uses samples of 30 banking firms listed in the Indonesian Stock Exchange during the year of 2013-2014. The method used is quantitative descriptives by analysing means and frequency distributions; testing the hypotheses by ways of individual parameter significance test (t test), simultaneous effect test (f test), classical assumption tests; Data normality, multicolinearity, autocorrelation test, and heterokedasticities; determination tests (R2) and multiple regression tests. The results show that Board of Commissioners has significant effect on the net profit margin. On the contrary, Independent Commissioners and Audit Committee have no significant effect on the net profit margin. Simultaneously, Board of Commissioners, Independent Commissioners and Audit Committee have no signifcant influence on the net profit margin.